PH measurement by sol-gel using clad optical fiber - Sana Mohammed Baleg, 1985-; Rosly Abdul Rahman, supervisor; Fakulti Sains (2010)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2010